Distinct Responses of Rare and Abundant Microbial Taxa to In Situ Chemical Stabilization of Cadmium-Contaminated Soil - Min Xu (American Society for Microbiology, 2021)

(untitled)
Understanding the ecological roles of rare and abundant species in the restoration of soil ecosystem functions is crucial to remediation of heavy metal-polluted soil. Our study assessed the efficiencies of five commonly used soil amendments on recovery of ecosystem multifunctionality and emphasized the relative contributions of rare and abundant microbial communities to ecosystem multifunctionality.